Leadership integrity and the role of human resource management in Greece: Gatekeeper or bystander?. (21st June 2018) - Tasoulis, Konstantinos; Krepapa, Areti; Stewart, Marcus M.
Abstract : With ethical misconduct commonplace in organizations and with the touting of competitive advantage associated with ethical organizational practices, considerable attention has turned to leadership integrity. Leaders are uniquely situated to influence the behavior of organizational members, and integrity has been shown to be instrumental in supporting ethical behavior and decision‐making. This article explores the role and influence of human resources management (HRM) in supporting leadership integrity among a group of large organizations operating in crisis‐stricken Greece. Although the institutional and cultural context of Greece appears to exacerbate role tensions confronted by human resources (HR) professionals, its forces are not deterministic; findings from in‐depth interviews with 12 HR directors indicate that the HR potential to secure ethical influence at the top level is primarily contingent on the nature of the organization's culture. Cultures of integrity enable HR executives to influence integrity and ethical behavior in top management teams (TMTs). In contrast, compliance‐based organizational cultures appear to breed a fickle HR presence: fostering integrity and ethical behavior for the middle and lower levels of an organization, while turning a blind eye to integrity violations at the top.